Airport low-reflection photovoltaic module
By depositing multiple layers of coatings in sequence on the surface of photovoltaic modules, optimizing optical and physical properties, the problems of high reflectivity and low environmental adaptability are solved, and low reflectivity, high light transmission and high efficiency energy output are achieved, suitable for harsh Airport applications in the environment.
Patent Information
- Application Number
- CN202411290089.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
Existing photovoltaic modules have shortcomings in high reflectivity, low photoelectric conversion efficiency and environmental adaptability, especially in harsh environments such as high temperature, high humidity and salt spray, which are difficult to maintain long-term and stable operation.
Using a multi-layer coating structure, including self-assembled single-molecular layer, high-refractive index layer, low-refractive index layer, vanadium-doped high-refractive index layer and fluorosilicon modified azophenyl group-containing conformal layer, through magnetization Preparation by sputtering coating and chemical vapor deposition methods to optimize optical and physical properties.
It achieves low reflectivity, high light transmittance and excellent environmental adaptability, enhances photoelectric conversion efficiency and long-term stability, and is suitable for special environmental conditions such as high-demand airports.
Smart Images

Figure BDA0005044295360000071 
Figure BDA0005044295360000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaics, and in particular to a low-reflection photovoltaic assembly for an airport. Background Art
[0002] With the transformation of the global energy structure and the demand for sustainable development, solar energy has developed rapidly as a clean and renewable energy source. Photovoltaic technology is an important way to utilize solar energy. The efficiency and performance of its core components, photovoltaic modules, directly affect the energy output of the entire system. However, photovoltaic modules of existing technologies still have some shortcomings in practical applications, especially in terms of high reflectivity, low photoelectric conversion efficiency and poor environmental adaptability.
[0003] Traditional photovoltaic modules cannot fully utilize the sunlight that hits the modules due to their high surface reflectivity, which limits the further improvement of photoelectric conversion efficiency. In addition, in harsh environments such as high temperature, high humidity, and salt spray, the performance and durability of the modules face severe challenges and are easily damaged, affecting long-term stable operation. In particular, in specific application scenarios, such as airports, higher requirements are placed on the optical performance and structural characteristics of photovoltaic modules, such as low light pollution, high light transmittance, and good environmental integration.
[0004] In view of the limitations of the prior art, the present invention provides a low-reflection photovoltaic module for an airport and a method for preparing the same, aiming to solve the above-mentioned problems through innovative structural design and material selection, thereby achieving low reflectivity, high photoelectric conversion efficiency and excellent environmental adaptability, and is particularly suitable for special environmental conditions such as airports that have high requirements on the performance of photovoltaic modules. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides an airport low-reflection photovoltaic module to solve the problems of the existing photovoltaic modules in terms of high reflectivity, low photoelectric conversion efficiency and poor environmental adaptability.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A low-reflection photovoltaic assembly for an airport, comprising a photovoltaic panel and a low-reflection coating coated on the photovoltaic panel; the low-reflection coating comprises a first self-assembled monolayer, a first high-refractive index layer, a low-refractive index layer, a second high-refractive index layer, a second self-assembled monolayer and a conformal layer deposited in sequence; the first self-assembled monolayer is deposited on the surface of the photovoltaic panel, and the conformal layer is arranged away from the surface of the photovoltaic panel; the conformal layer is a fluorosilicon-modified polymer containing azobenzene groups.
[0008] As a preferred technical solution, the first self-assembled monolayer is at least one of 4-(9H-carbazole-9-yl)phenylboronic acid, 3-(9H-carbazole-9-yl)phenylboronic acid, (9-ethyl-9H-carbazole-3-yl)boric acid, and 9H-carbazole-3-ylboric acid.
[0009] As a preferred technical solution, the first high refractive index layer is at least one of niobium pentoxide, titanium dioxide, and aluminum trioxide. The first high refractive index layer of the present invention can be prepared by using an existing magnetron sputtering coating method or a chemical vapor deposition CVD method or a sol-gel method to complete the coating of the film layer, which will not be described in detail here.
[0010] As a preferred technical solution, the low refractive index layer is silicon dioxide or magnesium fluoride. The low refractive index layer of the present invention can be prepared by using existing magnetron sputtering coating method or chemical vapor deposition CVD method or sol-gel method to complete the coating of the film layer, which will not be repeated here.
[0011] As a preferred technical solution, the second high refractive index layer is vanadium-doped niobium pentoxide or vanadium-doped aluminum oxide.
[0012] As a preferred technical solution, the second self-assembled monolayer is 3-aminopropyltrimethoxysilane or aminopropylmethyldiethoxysilane.
[0013] As a preferred technical solution, the fluorosilicone-modified polymer containing azobenzene groups is obtained by copolymerization of DMAAB monomer, methacrylate monomer and fluorine-containing acrylic cage-type polysilsesquioxane.
[0014] As a preferred technical solution, the methacrylate monomer is at least one of methyl methacrylate, isobornyl methacrylate, and dicyclopentyl methacrylate.
[0015] As a preferred technical solution, the fluorinated acrylic cage-type polysilsesquioxane is first obtained by using 3,3,3-trifluoropropyltrimethoxysilane as a raw material, obtaining a cage-type polysilsesquioxane intermediate through a hydrolysis reaction, and then adding a triethylamine solution of 1-methyl-2-(trimethoxysilyl)ethyl methacrylate to perform a ring-closing reaction to obtain it.
[0016] As a preferred technical solution, the molar ratio of the DMAAB monomer, the methacrylate monomer and the fluorinated acrylic cage-type polysilsesquioxane is 1-5:3-8:1-5.
[0017] The airport low-reflection photovoltaic module of the present invention achieves multiple technical effects through a series of innovative structural designs and material selections. First, the module includes multiple coatings deposited on the photovoltaic panel in sequence, from the self-assembled monolayer to the conformal layer, and each layer is optimized for specific optical and physical properties. The first self-assembled monolayer uses a specific compound to enhance adhesion to the photovoltaic panel, while the first high refractive index layer uses niobium pentoxide, titanium dioxide or aluminum oxide to increase the refraction of light and reduce reflection. The low refractive index layer uses silicon dioxide or magnesium fluoride to form a refractive index gradient to further reduce reflection. The second high refractive index layer uses vanadium-doped materials to increase the refractive index and light absorption, thereby enhancing the photoelectric performance. The second self-assembled monolayer uses a specific silane compound to enhance adhesion to the previous layer. The conformal layer uses a polymer containing azobenzene groups modified by fluorine silicon, which not only provides weather resistance, anti-pollution ability and self-cleaning properties, but also enhances the overall performance and environmental adaptability of the photovoltaic module. The conformal layer polymer of the present invention, due to the introduction of cage-type polysilsesquioxane (POSS) containing fluorine and silicon elements, on the one hand, thanks to its excellent thermal stability, significantly improves the temperature resistance of photovoltaic modules under high temperature environments; its rigid cage structure enhances the mechanical strength and wear resistance of the coating, making the assembly more durable; chemically inert POSS also improves the chemical stability of photovoltaic modules, provides additional ultraviolet protection, reduces photodegradation, and also enhances the environmental adaptability of photovoltaic modules, especially the stability under harsh environments such as humidity and salt spray. On the other hand, POSS containing fluorine and silicon elements reduces the surface energy of the coating, reduces the adhesion of dust and dirt, ensures the cleanliness of the photovoltaic panel, thereby maximizing the capture of light, and the high transparency POSS helps to maintain the high light transmittance of the photovoltaic module, further improving the photoelectric conversion efficiency. The conformal layer polymer of the present invention, at the same time, due to the introduction of azobenzene groups, brings photochromic properties to the polymer, which allows the photovoltaic module to automatically adjust its optical properties according to the illumination conditions, further improving the photoelectric conversion efficiency. Taken together, these properties of the conformal layer not only improve the performance of photovoltaic modules, but also improve their stability and reliability under harsh environmental conditions, providing an ideal photovoltaic solution for special application scenarios such as airports.
[0018] Beneficial effects of the present invention:
[0019] The airport low-reflection photovoltaic module of the present invention not only achieves low reflectivity and high light transmittance, but also enhances the environmental adaptability of the photovoltaic module by innovatively depositing multiple layers of coatings with specific optical properties on the surface of the photovoltaic panel. This design not only enhances the photoelectric conversion efficiency of the photovoltaic module, but also maintains the long-term stability and durability of the module, which helps to maintain efficient energy output under various environmental conditions.
[0020] In general, the low-reflection photovoltaic module for airports of the present invention not only has excellent photoelectric conversion efficiency and environmental adaptability, but also ensures its long-term durability and stability in harsh environments such as high temperature, high humidity, and salt spray. The overall comprehensive performance is strong, and it can meet the high standard requirements of photovoltaic modules in special application scenarios such as airports, ensuring the high efficiency and reliability of the photovoltaic system in long-term operation. DETAILED DESCRIPTION
[0021] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0022] Example 1
[0023] The airport low-reflection photovoltaic assembly of this embodiment includes a photovoltaic panel and a low-reflection coating coated on the photovoltaic panel; the low-reflection coating includes a first self-assembled monolayer, a first high refractive index layer, a low refractive index layer, a second high refractive index layer, a second self-assembled monolayer and a conformal layer deposited in sequence; the first self-assembled monolayer is deposited on the surface of the photovoltaic panel, and the conformal layer is arranged away from the surface of the photovoltaic panel; the conformal layer is a fluorosilicon-modified polymer containing azobenzene groups.
[0024] The first self-assembled monolayer is 4-(9H-carbazole-9-yl)phenylboronic acid.
[0025] The first high refractive index layer is niobium pentoxide.
[0026] The low refractive index layer is silicon dioxide.
[0027] The second high refractive index layer is vanadium-doped niobium pentoxide.
[0028] The second self-assembled monolayer is 3-aminopropyltrimethoxysilane.
[0029] In the process of preparing the first self-assembled monolayer (SAM layer) of this embodiment, the surface of the photovoltaic panel is first thoroughly cleaned, and deionized water combined with ultrasonic cleaning is used to remove oil stains, dust and other impurities, followed by a secondary cleaning with isopropanol to remove water-soluble residues, and blown dry with nitrogen to ensure that the surface is completely dry and free of organic pollutants. Next, a suitable solvent such as dimethylformamide (DMF) is selected, and the accurately weighed 4-(9H-carbazole-9-yl)phenylboronic acid is heated and dissolved to form a dilute solution with a concentration of between 0.5mM. The photovoltaic panel is immersed in the solution, ensuring complete immersion in a horizontal manner, and the self-assembly reaction is carried out in a dust-free environment for 3 hours. After the impregnation is completed, the photovoltaic panel is dried in a controlled environment to avoid contamination.
[0030] In this embodiment, the first high refractive index layer and the low refractive index layer are prepared by using the existing magnetron sputtering coating method to complete the coating of the film layer, which will not be described in detail here.
[0031] Preparation of the second high refractive index layer: Select high-purity niobium pentoxide (Nb 2 O 5 ) is used as the target material and 3% vanadium (V) is doped. Before sputtering, ensure that the vacuum chamber is clean and the vacuum degree reaches 10Pa. Then, argon gas is introduced into the vacuum chamber as the sputtering medium, and the target material and substrate are heated to 200°C. Next, a magnetic field is applied around the target material to form a high-density plasma. A DC power supply is applied to generate a voltage difference between the target material and the substrate, so that the argon ions are accelerated to hit the target material, and the sputtered target atoms pass through the plasma and are deposited on the substrate to form a thin film; the sputtering power is set to 500W, the working gas (argon) flow rate is 20sccm, and the sputtering time is controlled to 2 hours.
[0032] In the process of preparing the second self-assembled monolayer (SAM layer) in this embodiment, a suitable solvent ethanol is first selected to dissolve the accurately weighed 3-aminopropyltrimethoxysilane to form a dilute solution with a concentration between 1mM. The photovoltaic panel is immersed in the solution, and the photovoltaic panel is completely immersed in a horizontal manner, and the self-assembly reaction is carried out in a dust-free environment for 5 hours. After the immersion is completed, the photovoltaic panel is dried in a controlled environment to avoid contamination.
[0033] Preparation of conformal layer: firstly, DMAAB monomer, methyl methacrylate and fluorinated acrylic cage polysilsesquioxane are mixed in a molar ratio of 1:3:1, and an appropriate amount of initiator sodium persulfate (about 0.02wt% of the above mixture) is added, and the prepolymer solution is obtained after uniform mixing; the obtained prepolymer solution is coated on the second self-assembled monolayer, heated to 60°C, and copolymerized through a curing process to form a fluorine-silicon modified polymer conformal layer containing azobenzene groups. The DMAAB has a CAS registration number of 76961-11-0 and a Chinese name of 2-methyl-N-[4-[4-(2-methylprop-2-enoylamino)phenyl]azophenyl]prop-2-enoamide.
[0034] The fluorinated acrylic cage polysilsesquioxane is prepared by first adding 12 parts of 3,3,3-trifluoropropyltrimethoxysilane and 0.5 parts of sodium hydroxide to an aqueous solution of acetone with a mass concentration of 30% for hydrolysis to obtain a cage polysilsesquioxane intermediate, and then adding a triethylamine solution of 1-methyl-2-(trimethoxysilyl)ethyl methacrylate with a mass concentration of 20%, wherein the molar ratio of the 1-methyl-2-(trimethoxysilyl)ethyl methacrylate to the cage polysilsesquioxane intermediate is 1:1, and performing a ring-closing reaction to obtain a fluorinated acrylic cage polysilsesquioxane. Cage polysilsesquioxane, referred to as POSS, has a general formula (RSiO3 / 2 ) n , wherein R is a group connected to eight vertices of Si atoms. In the present invention, the fluorinated acrylic cage-type polysilsesquioxane has seven vertices connected to 3,3,3-trifluoropropyl groups and one vertice is methacrylate.
[0035] Example 2
[0036] The airport low-reflection photovoltaic assembly of this embodiment includes a photovoltaic panel and a low-reflection coating coated on the photovoltaic panel; the low-reflection coating includes a first self-assembled monolayer, a first high refractive index layer, a low refractive index layer, a second high refractive index layer, a second self-assembled monolayer and a conformal layer deposited in sequence; the first self-assembled monolayer is deposited on the surface of the photovoltaic panel, and the conformal layer is arranged away from the surface of the photovoltaic panel; the conformal layer is a fluorosilicon-modified polymer containing azobenzene groups.
[0037] The first self-assembled monolayer is 3-(9H-carbazole-9-yl)phenylboronic acid.
[0038] The first high refractive index layer is titanium dioxide.
[0039] The low refractive index layer is magnesium fluoride.
[0040] The second high refractive index layer is vanadium-doped aluminum oxide.
[0041] The second self-assembled monolayer is aminopropylmethyldiethoxysilane.
[0042] In the process of preparing the first self-assembled monolayer (SAM layer) in this embodiment, the steps are the same as those in Embodiment 1, except that 3-(9H-carbazole-9-yl)phenylboronic acid is used instead of 4-(9H-carbazole-9-yl)phenylboronic acid.
[0043] In this embodiment, the first high refractive index layer and the low refractive index layer are prepared by using the existing magnetron sputtering coating method to complete the coating of the film layer, which will not be described in detail here.
[0044] Preparation of the second high refractive index layer: Select high-purity aluminum oxide as the target material and dope it with 4% vanadium (V). Before sputtering, ensure that the vacuum chamber is clean and the vacuum degree reaches 10Pa. Then, introduce argon gas into the vacuum chamber as a sputtering medium, and heat the target and substrate to 250°C. Next, apply a magnetic field around the target to form a high-density plasma. Apply a DC power supply to generate a voltage difference between the target and the substrate, so that the argon ions are accelerated to hit the target, and the sputtered target atoms pass through the plasma and are deposited on the substrate to form a thin film; set the sputtering power to 500W, the working gas (argon) flow rate to 20sccm, and control the sputtering time to 2 hours.
[0045] In the process of preparing the second self-assembled monolayer (SAM layer) in this embodiment, the steps are the same as those in Embodiment 1, except that aminopropylmethyldiethoxysilane is used instead of 3-aminopropyltrimethoxysilane.
[0046] Preparation of the conformal layer: first, DMAAB monomer, isobornyl methacrylate and fluorinated acrylic cage-type polysilsesquioxane are mixed in a molar ratio of 2:6:3, and an appropriate amount of initiator sodium persulfate (approximately 0.02wt% of the above mixture) is added, and the prepolymer solution is obtained after mixing evenly; the obtained prepolymer solution is coated on the second self-assembled monolayer, heated to 60°C, and a copolymerization reaction is carried out through a curing process to form a fluorosilicone-modified polymer conformal layer containing azobenzene groups.
[0047] The fluorinated acrylic cage-type polysilsesquioxane is the same as that in Example 1.
[0048] Example 3
[0049] The airport low-reflection photovoltaic assembly of this embodiment includes a photovoltaic panel and a low-reflection coating coated on the photovoltaic panel; the low-reflection coating includes a first self-assembled monolayer, a first high refractive index layer, a low refractive index layer, a second high refractive index layer, a second self-assembled monolayer and a conformal layer deposited in sequence; the first self-assembled monolayer is deposited on the surface of the photovoltaic panel, and the conformal layer is arranged away from the surface of the photovoltaic panel; the conformal layer is a fluorosilicon-modified polymer containing azobenzene groups.
[0050] The first self-assembled monolayer is 9H-carbazole-3-ylboronic acid.
[0051] The first high refractive index layer is aluminum oxide.
[0052] The low refractive index layer is silicon dioxide.
[0053] The second high refractive index layer is vanadium-doped niobium pentoxide.
[0054] The second self-assembled monolayer is 3-aminopropyltrimethoxysilane.
[0055] In the process of preparing the first self-assembled monolayer (SAM layer) in this embodiment, the steps are the same as those in Embodiment 1, except that 9H-carbazole-3-ylboronic acid is used instead of 4-(9H-carbazole-9-yl)phenylboronic acid.
[0056] In this embodiment, the first high refractive index layer and the low refractive index layer are prepared by using the existing magnetron sputtering coating method to complete the coating of the film layer, which will not be described in detail here.
[0057] Preparation of the second high refractive index layer: Select high-purity niobium pentoxide (Nb 2 O 5) is used as the target material and 5% vanadium (V) is doped. Before sputtering, ensure that the vacuum chamber is clean and the vacuum degree reaches 10Pa. Then, argon gas is introduced into the vacuum chamber as the sputtering medium, and the target material and substrate are heated to 200°C. Next, a magnetic field is applied around the target material to form a high-density plasma. A DC power supply is applied to generate a voltage difference between the target material and the substrate, so that the argon ions are accelerated to hit the target material, and the sputtered target atoms pass through the plasma and are deposited on the substrate to form a thin film; the sputtering power is set to 500W, the working gas (argon) flow rate is 15sccm, and the sputtering time is controlled to 3 hours.
[0058] The preparation of the second self-assembled monolayer (SAM layer) in this example is the same as that in Example 1.
[0059] Preparation of the conformal layer: first, DMAAB monomer, dicyclopentyl methacrylate and fluorinated acrylic cage polysilsesquioxane are mixed in a molar ratio of 5:8:5, and an appropriate amount of initiator sodium persulfate (approximately 0.02wt% of the above mixture) is added, and the prepolymer solution is obtained after mixing evenly; the obtained prepolymer solution is coated on the second self-assembled monolayer, heated to 60°C, and a copolymerization reaction is carried out through a curing process to form a fluorine-silicon-modified polymer conformal layer containing azobenzene groups.
[0060] The fluorinated acrylic cage-type polysilsesquioxane is the same as that in Example 1.
[0061] Comparative Example 1
[0062] The raw material composition and preparation steps of the airport low-reflection photovoltaic module of this comparative example are basically the same as those of Example 1, except that the photovoltaic module of this comparative example does not include a conformal layer.
[0063] Comparative Example 2
[0064] The raw material composition and preparation steps of the airport low-reflection photovoltaic module of this comparative example are basically the same as those of Example 1, except that the conformal layer of the photovoltaic module of this comparative example does not include DMAAB monomer to participate in the reaction.
[0065] Comparative Example 3
[0066] The raw material composition and preparation steps of the airport low-reflection photovoltaic module of this comparative example are basically the same as those of Example 1, except that the photovoltaic module of this comparative example does not include the first self-assembled monolayer and the second self-assembled monolayer.
[0067] The airport low-reflection photovoltaic modules prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests, and the performance results are shown in Table 1:
[0068] Among them, reflectivity test: According to the international standard IEC 60904-3, the reflectivity of photovoltaic modules is measured using an integrating sphere spectral reflectivity meter.
[0069] Light transmittance test: The light transmittance is evaluated by measuring the spectral transmittance of the photovoltaic module, specifically measuring the spectral transmittance of the photovoltaic module within a specific wavelength range (such as the visible light range of 380nm to 780nm).
[0070] Photoelectric conversion efficiency test: According to the international standard IEC 61215, the components are tested under standard test conditions, that is, at 1000W / m 2 The results are given under the following conditions: light intensity, ambient temperature of 25°C and spectrum conditions of AM 1.5 (air quality).
[0071] Environmental adaptability test: including high and low temperature cycle test (international standard IEC 61215, the component undergoes 1000 temperature cycles, each cycle is from -40℃ to +85℃), damp heat test (international standard IEC 61646, the component is exposed to 85% relative humidity and 85℃ temperature for 1000 hours) and salt spray test (international standard IEC 61701, the component is exposed to salt spray environment for 1000 hours); among them, high and low temperature resistance and damp heat resistance are evaluated by testing the drop in reflectivity to evaluate the performance changes of the component under different environmental conditions, and salt spray resistance is evaluated by observing surface corrosion to evaluate the performance changes of the component.
[0072] Self-cleaning properties test: Evaluated by measuring the contact angle of the component surface.
[0073] Weathering test: According to the ultraviolet irradiation test (international standard ISO 4892-3, exposure for 500 hours), the stability of the material after long-term exposure to sunlight is evaluated by testing the decrease in reflectivity. Table 1 The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.
Claims
1. A low-reflection photovoltaic module for airports, It is characterized in that The photovoltaic module includes a photovoltaic panel and a low-reflection coating coated on the photovoltaic panel; the low-reflection coating includes a first self-assembled monolayer, a first high refractive index layer, a low refractive index layer, a second high refractive index layer, a second self-assembled monolayer and a conformal layer deposited in sequence; the first self-assembled monolayer is deposited on the surface of the photovoltaic panel, and the conformal layer is arranged away from the surface of the photovoltaic panel; the conformal layer is a fluorine-silicon modified polymer containing azobenzene groups.
2. The low-reflection photovoltaic module for airports as claimed in claim 1, It is characterized in that The first self-assembled monolayer is at least one of 4-(9H-carbazole-9-yl)phenylboronic acid, 3-(9H-carbazole-9-yl)phenylboronic acid, (9-ethyl-9H-carbazole-3-yl)boric acid, and 9H-carbazole-3-ylboric acid.
3. The low-reflection photovoltaic module for airports as claimed in claim 1, It is characterized in that The first high refractive index layer is at least one of niobium pentoxide, titanium dioxide, and aluminum oxide.
4. The low-reflection photovoltaic module for airports as claimed in claim 1, It is characterized in that The low refractive index layer is silicon dioxide or magnesium fluoride.
5. The low-reflection photovoltaic module for airports according to claim 1, It is characterized in that The second high refractive index layer is vanadium-doped niobium pentoxide or vanadium-doped aluminum oxide.
6. The low-reflection photovoltaic assembly for an airport as claimed in claim 1, It is characterized in that The second self-assembled monolayer is 3-aminopropyltrimethoxysilane or aminopropylmethyldiethoxysilane.
7. The low-reflection photovoltaic assembly for an airport as claimed in claim 1, It is characterized in that The fluorine-silicon-modified polymer containing azobenzene groups is obtained by copolymerization of DMAAB monomer, methacrylate monomer and fluorine-containing acrylic cage-type polysilsesquioxane.
8. The low-reflection photovoltaic assembly for an airport as claimed in claim 1, It is characterized in that The methacrylate monomer is at least one of methyl methacrylate, isobornyl methacrylate, and dicyclopentyl methacrylate.
9. The low-reflection photovoltaic assembly for an airport as claimed in claim 1, It is characterized in that The fluorinated acrylic cage-type polysilsesquioxane is obtained by first using 3,3,3-trifluoropropyltrimethoxysilane as a raw material, performing a hydrolysis reaction to obtain a cage-type polysilsesquioxane intermediate, and then adding a triethylamine solution of 1-methyl-2-(trimethoxysilyl)ethyl methacrylate to perform a ring-closing reaction to obtain the fluorinated acrylic cage-type polysilsesquioxane.
10. The low-reflection photovoltaic assembly for airport according to claim 1, It is characterized in that The molar ratio of the DMAAB monomer, the methacrylate monomer and the fluorine-containing acrylic cage-type polysilsesquioxane is 1-5:3-8:1-5.
